Predictors of pleural complications in trauma patients undergoing tube thoracostomy: A prospective observational study - NASCIMENTO,ISIS KOBASHIGAWA DO (2022)
ABSTRACT Objective: to identify variables related to pleural complications in patients undergoing tube thoracostomies due to traumatic injuries. Method: we conducted a prospective observational study from May/2019 to January/2021 including adult trauma patients submitted to tube thoracostomies after hospital admission. Patients undergoing thoracotomies as the initial treatment were not included. We excluded patients with suspected and confirmed COVID-19 diagnosis during the hospitalization. Pleural complications were defined as clotted hemothorax, residual pneumothorax and empyema. Students t, Mann Whitneys, Chi square and Fishers exact test were used to compare variables between groups. We considered p<0.05 as significant. Results: we analyzed 68 patients. The mean age was 36.0 + 12.6 years and 91.2% were male. The mean RTS and ISS were, respectively, 7.0 ± 1.6 and 15.9 ± 7.6. The most frequent trauma mechanism was stab wounds in 50.0%, followed by blunt trauma in 38.2%. The severity of thoracic injuries was stratified (AIS) as 2 (4.4%), 3 (80.9%), 4 (13.2%), e 5 (1.5%). Pleural complications happened in 14 (20.5%) patients, being clotted / residual hemothorax (11.8%), residual pneumothorax (4.4%), empyema (2.9%) and miscellaneous (1.4%). These patients were treated by thoracoscopy (5), thoracotomy (3), chest re-drainage (3) and clinical measures alone (3). There was a significant association between pleural complications with the time of permanence (p<0,001) and the necessity of relocation (p<0,001) of the drain. Conclusion: the predictors of pleural complications in this series were time of permanence and the necessity of relocation of the drain.